Hubungan Pengetahuan Gizi Dan Konsumsi Western Fast Food (Frekuensi Dan Sumbangan Energi) Dengan Status Gizi Remaja Di Smp Muhammadiyah 10 Surakarta - Khasanah, Nur; , Susi Dyah Puspowati, SP., M.Si; , Dyah Widowati, SKM (2014)
Background : Nutrition knowledge influencing selection and food habits. Western fast food in Indonesia is growing rapidly turned out to be appreciated by the public, especially children and adolescents. However, western fast food contains high calories, fat and low in fiber if consumption overload can cause of obesity. Objective : To know the relationship between nutrition knowledge, western fast food consumption rate (frequency and energy contribution) and nutritional status in adolescents in SMP Muhammadiyah 10 Surakarta. Methods : Observational research using cross sectional approach. Technique of sampling was taken by employing stratified random sampling. Total sample of 45 students of class VII and VIII. Data nutritional knowledge was measured using a questionnaire, frequency and energy of western fast food contribution using FFQ, and nutritional status using anthropometry. Analysis of the relationship used the Pearson product moment correlation test. Result : The research results show that the subject with enough nutrition knowledge (44,4%), the frequency of consumption of western fast food considered being often and very often (40%), the energy contribution of western fast food was mostly good (93,3%), and 57,8% of respondents have normal nutrition status. The test results pearson product moment correlation nutrition knowledge and nutritional status obtained p=0,463. The test result of relationship frequencies western fast food consumption and nutritional status obtained p=0,092. The test result of relationship contribution energy western fast food and nutritional status obtained p=0,025. Conclusion : There is no relationship between nutrition knowledge and nutritional status (p=0,463), there was no association frequency of consumption of western fast food with nutritional status (p=0,092), and no correlation beween energy contribution of western fast food and nutritional status (p=0,025).